2018
DOI: 10.1097/tp.0000000000002194
|View full text |Cite
|
Sign up to set email alerts
|

IL-34 Inhibits Acute Rejection of Rat Liver Transplantation by Inducing Kupffer Cell M2 Polarization

Abstract: IL-34 plays an important role in KC M2 polarization-dependent AR inhibition of rat liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 57 publications
4
40
0
Order By: Relevance
“…Similarly, Zhao et al. found that IL‐34 was effective to inhibit acute rejection and prolong the recipients’ survival by altering the polarization of Kupffer cells polarization into an M2‐phenotype in a liver transplantation model in rats . Additionally, IL‐34 can be used as an ex vivo cytokine for the generation of immunosuppressive immune cells that can be utilized as adjuvant cell therapy to prolong survival of implanted grafts.…”
Section: Il‐34 From Bench To Bedsidementioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, Zhao et al. found that IL‐34 was effective to inhibit acute rejection and prolong the recipients’ survival by altering the polarization of Kupffer cells polarization into an M2‐phenotype in a liver transplantation model in rats . Additionally, IL‐34 can be used as an ex vivo cytokine for the generation of immunosuppressive immune cells that can be utilized as adjuvant cell therapy to prolong survival of implanted grafts.…”
Section: Il‐34 From Bench To Bedsidementioning
confidence: 97%
“…In Kupffer cells, IL‐34 alters Kupffer cells polarization into an M2‐phenotype, characterized by decreased expression of pro‐inflammatory cytokines such as IL‐12, and increased expression of immunosuppressive cytokines, including Arg‐1, IL‐10, and TGF‐β1. The responsible mechanism was mediated by the IL‐34‐induced activation of the PI3K/Akt pathway, enhancement of the phosphorylation of mTOR, S6K, and 4E‐BP, and suppression of p65 and p38 MAPK activation …”
Section: Biological Functions Of Il‐34mentioning
confidence: 99%
“…Furthermore, macrophages differentiated from human peripheral blood monocytes with IL-34 exhibit greater resistance to HIV-1 infection than those derived from CSF1 due to increased expression of pertinent restriction factor genes 101 . IL-34 has also been demonstrated to repolarize rat M1 Kupffer cells (KCs) in the liver to the M2 phenotype by activating the PI3K/ protein kinase B/mammalian target of rapamycin (mTOR) pathway and could be used therapeutically to reduce acute rejection during liver transplantation 102 . Each of these ligands might play a different role in osteoclasts and other myeloid cells, which are discussed below.…”
Section: Csf1r Ligands and Their Differential Functions In Csf1r Signmentioning
confidence: 99%
“…In acute infection, overdose of hepatotoxic drugs, and liver IRI, KCs are activated by DAMPs via TLR3, TLR4, and TLR9 and polarized to the M1 phenotype, which induces proinflammatory cascades and infiltration of monocytes, neutrophils, and T lymphocytes, which exacerbate liver injury [26][27][28]. In our previous studies, we found that blocking the M1 KC polarization or promoting the KCs M2 polarization reduced liver IRI and organ rejection [18,29,30].…”
Section: Discussionmentioning
confidence: 97%